PERANCANGAN APLIKASI MOBILE TEMPAT WISATA (Studi Kasus: WILAYAH BANDUNG) - Budiman . (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2018)
The use of smartphones provide benefits to society, all information can be accessed easily through a smartphone. Bandung is the capital of Paris Van Java, Bandung is famous for its beauty and coolness. Bandung has many tourist attractions some of which not yet known by travelers who will pay a visit to Bandung include nature tours, culinary, shopping and hotels. In addition tourists visiting the difficulty to get to tourist attractions because it is not yet equipped with Google Maps. Research methodology undertaken consists of several stages, namely the planning phase, the design phase and needs analysis application. At each stage there are some tasks that are carried out so that the dirancangan system to suit your needs. Based on the design of the application is done, then the design of the application of these sights can provide information to travelers about tourist attractions in the area of Bandung and the use of the Google Maps feature on these applications can give ease for tourists to visit tourist attractions to be visited. The design of this application can be implemented on other area attractions. Keywords: Design, Application, Tour, Android